Phenotypic and genotypic characterization of four factor VII deficiency patients from central China. Issue 4 (June 2015) - Liu, Hui; Wang, Hua-Fang; Cheng, Zhi-peng; Wang, Qing-yun; Hu, Bei; Zeng, Wei; Wu, Ying-ying; Guo, Tao; Tang, Liang; Hu, Yu
Abstract : Hereditary coagulation factor VII deficiency (FVIID) is a rare autosomal, recessive inherited hemorrhagic disorder related to a variety of mutations or polymorphisms throughout the factor VII (FVII) gene ( F7 ). The aims of this study were to characterize the molecular defect of the F7 gene in four unrelated patients with FVIID and to find the genotype–phenotype correlation. All nine exons, exon–intron boundaries, and 5' and 3'-untranslated regions of the F7 gene were amplified by PCR and the purified PCR products were sequenced directly. Suspected mutations were confirmed by another PCR and sequencing of the opposite strand. Family studies were also performed. A total of five unique lesions were identified, including three missense mutations (c.384A>G, c.839A>C, c.1163T>G, predicting p.Tyr128Cys, p.Glu280Ala and p.Phe388Cys substitution, respectively) and two splice junction mutations (c.572–1G>A, c.681+1G>T), among which two (p.Glu280Ala, p.Phe388Cys) were novel. A previously reported mutation p.Tyr128Cys was seen in the homozygous state in two unrelated patients. The other two cases were both compound heterozygotes of a missense mutation and a splicing site mutation. Multiple sequence alignment using DNAMAN analysis showed that all the missense mutations were found in residues that highly conserved across species and vitamin K-dependent serine proteases. Online software Polyphen and SIFT were used to confirm the pathogenic of the missense mutation. p.Tyr128Cys seems to be a hotspot of the F7 gene in ethnic Han Chinese population.